Case Report: Early diagnosis and bevacizumab-based chemotherapy for primary pericardial mesothelioma: a case with occupational asbestos exposure history - Wang, Daniel; Wang, Yung Hsuan; Chu, Sung Chao (Frontiers in Cardiovascular Medicine, 2023)
Background Primary pericardial mesothelioma (PPM) is an exceedingly rare malignant cancer and has a poor prognosis, which has been partly attributed to its frequently delayed diagnosis due to its nonspecific syndromes, its similar presentation to benign pericardial diseases, and its non-definitive etiology. In many PPM cases, the time from presentation to definite diagnosis may last for several months or even over one year. Unlike pleural mesothelioma, the relationship between PPM and asbestos exposure remains unsettled. To date, there is no consensus on the treatment of PPM. Case report The patient is a 57-year-old male who had nonspecific syndromes and inconclusive image findings. The occupational long-term asbestos exposure history of this patient raised our concerns regarding potential malignancy when confronted with unexplained pericardial effusion accompanied by cardiac tamponade. The heightened suspicion prompted us to perform pericardiocentesis and biopsy on the third day after admission to our department. An early diagnosis of PPM was established by the pathological and immunohistochemical evaluation of the biopsy specimen two weeks after admission. Positron emission tomography-computed tomography revealed that the lesion was localized at the anterior part of the mediastinum without distant metastasis. This patient refused to receive cardiac surgery. He subsequently underwent six cycles of chemotherapy (cisplatin plus pemetrexed) in combination with bevacizumab (a humanized anti-VEGF antibody) as the first-line treatment, resulting in complete relief of symptoms and satisfactory outcomes with no complications. Four months after the first course, the patient initiated a second course of chemotherapy with a similar regimen, but he opted to discontinue the medical treatment after the initiation of the second course. The patient was transferred to the hospice care unit and unfortunately expired one year after the initial presentation. Conclusion We present a case of an early multidisciplinary clinical approach to diagnose and manage PPM with consideration of occupational asbestos exposure history and clinical symptoms. Bevacizumab-based chemotherapy remains an option for the treatment of PPM.